Emotions and Self-efficacy as Mediators of Pre-Service Teachers' Adoption of Digital Tools - Daher, Wajeeh; Baya'a, Nimer; Anabousy, Ahlam (Emerging Science Journal, 2021)
The present research examines whether the pre-service teachers’ preparation in using digital tools in their teaching develops their acceptance of these tools for teachings. The research also examines the mediation of self-efficacy, anxiety of using digital tools for teaching mathematics and science and enjoyment of this use between the constructs of acceptance of digital tools for teaching. We used the TAM questionnaire in addition to scales that measure enjoyment, self-efficacy and anxiety. Forty-eight mathematics and science pre-service teachers participated in the study. We analyzed the collected data using SPSS 21. The research results indicate that the pre-service teachers’ preparation resulted in significant differences in their scores of affective and usage constructs associated with their acceptance of digital tools for mathematics and science teaching, except in the scores of anxiety. Self-efficacy proved to be a partial mediator between attitude and intention-to-use. Enjoyment proved to be a partial mediator between ease-of-use and attitude, but not between usefulness and attitude. Moreover, enjoyment proved to be a partial mediator between attitude and intention-to-use. These findings contribute to the understanding of mediators that affect the acceptance of digital tools for teaching. Doi: 10.28991/esj-2021-01301 Full Text: PDF